2020
DOI: 10.1002/fsn3.1702
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fermentation and camellia oil emulsification characteristics of konjac glucomannan octenyl succinate

Abstract: It is important to select an appropriate emulsifier to overcome the poor stability and dispersibility of the vegetable oils in food system. Previous studies suggest that OSA‐modified konjac glucomannan (KGOS) has potential to be used as a food emulsifier. In this study, in vitro fermentation suggested that KGOS could promote the growth of the important intestinal probiotics Lactobacillus and Bifidobacterium and then promote intestinal fermentation to produce gas an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…During microencapsulation preparation, the wall material selection is vitally important 14 . Polysaccharides and their derivatives (such as gum arabic (GA), β‐cyclodextrin (β‐CD), octenyl succinic anhydride‐modified starch (OSAS) and konjac glucomannan octenyl succinate (KGOS)), 10–13,15 and proteins and their derivatives (such as soy protein isolate (SPI), whey protein isolate (WPI) and egg white protein isolate (EPI)), are the most widely applied wall materials in microcapsule preparation 16–18 . A previous study indicated that the hydrophobic cavity of β‐cyclodextrin (β‐CD) could protect the active compounds of essential oils against environmental conditions 19 .…”
Section: Introductionmentioning
confidence: 99%
“…During microencapsulation preparation, the wall material selection is vitally important 14 . Polysaccharides and their derivatives (such as gum arabic (GA), β‐cyclodextrin (β‐CD), octenyl succinic anhydride‐modified starch (OSAS) and konjac glucomannan octenyl succinate (KGOS)), 10–13,15 and proteins and their derivatives (such as soy protein isolate (SPI), whey protein isolate (WPI) and egg white protein isolate (EPI)), are the most widely applied wall materials in microcapsule preparation 16–18 . A previous study indicated that the hydrophobic cavity of β‐cyclodextrin (β‐CD) could protect the active compounds of essential oils against environmental conditions 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The BJH pore size distribution curve derived from the desorption branch features a narrow maximum in the ∼3 to ∼4.5 nm mesoporous range (3.9 nm BJH average pore diameter) suggesting homogenous pore diameters as well as high uniformity mesopores [55,56] . Furthermore α ‐MnO 2 displays high BJH cumulative pore volume and BET specific surface area of 0.223 cm 3 g −1 and 214.6 m 2 g −1 , respectively, the latter being the highest BET specific surface area for an α ‐MnO 2 with reasonably distinct crystallinity ever reported so far [22,57–71] …”
Section: Resultsmentioning
confidence: 86%
“…Figure 1(D) shows that at a certain total solids content (X 3 ), EE first increased and then decreased with an increasing homogenization rate (X 4 ) but the change was not obvious. The increase in total solid content increased the emulsion viscosity, which increased the EE 31‐33 …”
Section: Resultsmentioning
confidence: 99%
“…The increase in total solid content increased the emulsion viscosity, which increased the EE. [31][32][33] After optimization of the EE for ZBEO preparation, the optimized parameters obtained by RSM were: ratio of core to wall, 1:7.69; ratio of HPCD to SPI, 4.06; total solids content, 12%, and homogenization speed, 11 999 rpm. The reliability of the optimum conditions proposed was tested by conducting experiments with these parameters.…”
Section: Optimization Of Zbeo Microcapsule Preparation By Rsm Experim...mentioning
confidence: 99%